INNOVATION OF STUDENT CENTERED LEARNING MODEL BASED ON MICROBLOGGING EDMODO - Pirman Ginting; Yenni Hasnah; Mutia Febriyana (UIN Sumatera Utara Medan, 2020)
This study aims to produce an innovative learning model based on Microblogging Edmodo. This research was conducted through the application of Research and Development (R&D) methods which included several stages of research, it is started from designing SCL learning models based on microblogging edmodo, validation, and trials (small and large scale). The results of the study showed that the innovation of student-centered learning models based on edmodo e-learning microblogging was feasible to be applied in the learning process. It can be seen from the validation reaches 79.16%. The feasibility of the application is also strengthened by the increasing of the average percentage from audience validation. It results of 77.33% in small-scale trials and 91.30% in large-scale trials. This percentage shows that SCL learning models based on e-learning microblogging edmodo can be applied to students